Content and Language Integrated Learning (CLIL) Approach across Curriculum in Science Classrooms: Are the English Language Use and Learning Reveal? - Nurhamsi Deswila; Martin Kustati; Besral Besral; Syayid Sandi Sukandi (Yayasan Keluarga Guru Mandiri, 2020)
The study aims to reveal the implementation CLIL approach in improving students’ English language use and learning in the science classroom. A descriptive study was employed where data were collected using observation and interview to two classes at of Private Islamic Boarding in West Sumatera. The students for CLIL Strategy are the first grade of junior high school at science classrooms. The result of the research revealed that the use of the CLIL strategy across the curriculum is an effective strategy to develop English language use and learning. The pedagogical implications of the study for the EFL students in science classrooms include the need for teachers to consider underlying theories of teaching English in EFL context taking into account students’ constraints; a focus on the various types of students’ English ability and consider students’ interest in topic selection; teachers to be aware of the significance of the relationship between their attitude and background in classroom practice; teachers to be trained formally on the implementation of the CLIL Strategy.